THE EFFECT OF GOOD AGRICULTURAL PRACTICES (GAP) ADOPTION ON THE BUSINESS SUSTAINABILITY OF POTATO CULTIVATION IN GARUT REGENCY - Nabila An Nadjib; Anna Fatchiya; Dwi Sadono (Jurnal Mahasiswa Agribisnis, 2026)
The sustainability of potato farming in the highlands faces challenges due to less environmentally friendly conventional cultivation practices and suboptimal productivity. The adoption of Good Agricultural Practices (GAP) is an approach to improving business performance while supporting sustainability. This study aims to analyze the level of GAP adoption, the level of business sustainability of potato cultivation, and the effect of GAP adoption on business sustainability in Garut Regency. The study used a quantitative approach with a survey method of 125 potato farmers selected using proportionate stratified random sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that the level of GAP adoption was in the high category (50.2%). However, several components, such as the use of certified seeds, soil management, balanced fertilization, and integrated pest control remains suboptimal due to constraints such as cost, input availability, and cultivation practices. The level of business sustainability was also in the high category (50.4%), with the environmental aspect showing the highest achievement. The adoption of GAP had a positive and significant effect on business sustainability with an R² value of 0.367, indicating that GAP was able to explain 36.7% of the variation in business sustainability. These results confirm that GAP adoption plays a crucial role in supporting the sustainability of potato farming. However, support from other factors beyond the technical aspects of cultivation is still needed. The implications of this research encourage the systematic and ongoing strengthening of GAP support to ensure the sustainability of potato farming in the Garut highlands.